2020
DOI: 10.1017/s1930297500006896
|View full text |Cite
|
Sign up to set email alerts
|

This way, please: Uncovering the directional effects of attribute translations on decision making

Abstract: The translation of choice attributes into more meaningful information (e.g., from kWh to costs) is a form of choice architecture that is thought to facilitate decision making by providing decision signposts that activate personally relevant but latent objectives and guide decisions towards options that are most congruent with the activated objectives. Here, we investigated the psychological mechanisms that underlie and drive the directional effects of attribute translations on decision making. Across two choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…The information provided by decision assistance interventions must be evaluated based on personal values and goals to determine the utility of available options. 28,42 Incorporating behavioral scientific insights into interventions can improve the effectiveness of nudges. 36,37,[43][44][45] The manipulations involved in the studies included enhanced implementation intention (eg, setting deadlines for desirable behaviors), changed wording to increase the perceived value, and a combination of simplification, behavioral instruction, enhanced personal salience, and implementation intention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The information provided by decision assistance interventions must be evaluated based on personal values and goals to determine the utility of available options. 28,42 Incorporating behavioral scientific insights into interventions can improve the effectiveness of nudges. 36,37,[43][44][45] The manipulations involved in the studies included enhanced implementation intention (eg, setting deadlines for desirable behaviors), changed wording to increase the perceived value, and a combination of simplification, behavioral instruction, enhanced personal salience, and implementation intention.…”
Section: Discussionmentioning
confidence: 99%
“…36,37,[43][44][45] The manipulations involved in the studies included enhanced implementation intention (eg, setting deadlines for desirable behaviors), changed wording to increase the perceived value, and a combination of simplification, behavioral instruction, enhanced personal salience, and implementation intention. 36,37,[42][43][44][45] On the basis of the wording presented in the reminder letter, recipients might not consider it to be a serious problem and worthy to bring up this issue during their physician visits. Furthermore, patients would not challenge physician's authority, as discussing prescription appropriateness could be seen as offensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we did not investigate individual differences that could provide insights into how default units and personal relevance of a unit could influence the evaluations of numerical information. Previous research has shown that translations of attributes can act as decision signposts, depending for example on consumer values (Mertens, Hahnel & Brosch, 2019;Ungemach et al, 2018). Consumers with high environmental values were more sensitive to differences when numerical attributes were presented in a unit related to environmental consequences, like a CO 2 rating.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%